Faktor-Faktor yang Mempengaruhi Keberhasilan Program Pembenihan Skala Rumah Tangga di Kabupaten Padangsidimpuan Angkola Julu Padangsidimpuan Kota Provinsi Sumatera Selatan - Hotnur Anisyah Siregar; Firman Nugroho; Ridar Hendri (JURNAL SOSIAL EKONOMI PESISIR, 2020)
This study aimed to analyze the factors that affect the success rate of program household scale seedind in the District of Angkola Julu Padangsidimpuan city. This study uses was a quantitative approach. The population of this study is fish culvator which consists of 30 people take by census sampling technique. The data collection was done using questionnaires, interviews, and documentation. The data were analyzed with descriptive statistical analysis techniques using percentages, while the research hypothesis testing using the F test and t test were processed with SPSS. The results explained that the level of success of the household scale program in the succes category (81,01%). F-test (sig= 0,000<0,05)indicates that the variable communication, resources, dispitition and bureaucration structures together have a positive influence on the success of household scale program.